Thennodynamics Of Iron Reduction From Metallurgical Residues - Ivan Imris (The Minerals, Metals and Materials Society, 2003)
The iron production has generated many tonnes of very fine residues with high concentration of iron. In addition, during the recycling of galvanised steel scrap in the steel making processes the zinc and lead are largely concentrated in the dust. These kinds of dusts are usually dumped beside the metallurgical plants and cause environmental problems. Therefore the metal recovery from the metallurgical residues has become a major interest not only from the viewpoint of metals recycling but mainly from the viewpoint of environmental land protection. The thermodynamic analyses and laboratory experiments suggested that the metals could be recovered from metallurgical wastes by reduction roasting and by plasma smelting processes. The iron rich pellets with very high metallization may be obtained from metallurgical wastes by the reduction roasting and the inert slag and pig iron could be produced by plasma smelting processes. In both cases the iron rich products are suitable for the steel production. During the reduction roasting or plasma smelting the high volatile zinc and lead metals were removed and enriched as a secondary dust, Zn-Pb concentrate, which is suitable for processing in zinc and lead smelters. Suggested processes are commercially feasible and environmentally friendly without any solid or liquid waste.